2017
DOI: 10.1016/j.jsat.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and body composition of stimulant users: A baseline analysis of the STRIDE cohort

Abstract: Introduction Relatively little has been reported about the physical characteristics, such as cardiorespiratory fitness (CRF) and body composition, of stimulant users. Identifying risk factors associated with the physical health of stimulant users is an important public health issue as new treatments should better address the entire range of health concerns experienced by this population. Methods We examined cross-sectional data gathered at baseline from the STimulant Reduction Intervention using Dosed Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As for cardiovascular consequences, cocaine can cause increased heart rate and blood pressure, endothelial dysfunction, arrhythmia, and atherosclerosis. Combining cocaine with other substances (such as alcohol, marijuana, and/or tobacco) and other risk factors, such as overweight and obesity, can cause cumulative health damage 26,40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for cardiovascular consequences, cocaine can cause increased heart rate and blood pressure, endothelial dysfunction, arrhythmia, and atherosclerosis. Combining cocaine with other substances (such as alcohol, marijuana, and/or tobacco) and other risk factors, such as overweight and obesity, can cause cumulative health damage 26,40…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a pilot study conducted by our group found high rates of normal-weight and overweight crack users at hospital admission 25. Considering that overweight is associated with multiple medical conditions, including diabetes, hypertension, and hyperlipidemia, the increased risk of morbidity and mortality could be particularly harmful when combined with the use of stimulants such as cocaine 15,26…”
Section: Introductionmentioning
confidence: 96%
“…Both male and female participants in our study stated that they did not participate in exercise because of concerns with their poor overall health and the damage that drug use for many years may have done to their bodies. Only a few studies have measured fitness in people with SUD and found that cardiopulmonary fitness levels appear to be at least 15–30% lower in men and 25–40% lower in women with a SUD compared to normative values in people without a SUD of similar age ( Flemmen and Wang, 2015 , Stoutenberg et al, 2017 ). Although the underlying mechanisms for decreased fitness are not well known, they likely involve damage to cardiac and pulmonary tissue from smoking and misusing other substances.…”
Section: Discussionmentioning
confidence: 99%
“…People with OUD may face additional challenges in adhering and complying to an exercise program. Although people with SUD in general have been shown to have lower cardiorespiratory fitness than those without SUD of similar age and biological sex ( Flemmen and Wang, 2015 , Stoutenberg et al, 2017 ), people with OUD may have even lower fitness levels due to higher rates of smoking ( Gubner et al, 2018 ) and cardio-metabolic complications from long-term heroin and other opioid misuse ( Greenwald et al, 2021 ). In addition, although exercise has been shown to induce a hypoalgesic response and is an approved frontline, non-pharmacological treatment for chronic pain ( Dowell et al, 2016 ), chronic pain in people with OUD has been associated with a heightened sensitivity to pain and a fear that pain may be exacerbated by movement such as exercise ( Luque-Suarez et al, 2019 , Martel et al, 2013 , Wachholtz and Gonzalez, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers unique to the physical health and conditioning of individuals with SUD may require special attention. Although there are only a few studies that have measured fitness in people with SUD, cardiopulmonary fitness levels appear to be at least 15% to 30% lower in men and 25% to 40% lower in women with an SUD compared with their counterparts without SUD of similar age (29,30). The decrease in fitness may be attributed to several factors including a lack of participation in exercise (30).…”
Section: Introductionmentioning
confidence: 99%